The difference between Bali cattle and Limousin-Bali (Limbal) crossed cattle concerning their qualitative characteristics in Lombok Tengah District, Indonesia - ADI TIYA WARMAN; PANJONO PANJONO; GALIH TRIE FADHILAH; BAYU ANDRI ATMOKO; SIGIT BINTARA; TRI SATYA MASTUTI WIDI; ENDANG BALIARTI; ZAENAB NURUL JANNAH (Smujo International, 2024)
Abstract. Warman AT, Panjono, Fadhilah GT, Atmoko BA, Bintara S, Widi TSM, Baliarti E, Jannah ZN. 2024. The difference between Bali cattle and Limousine-Bali (Limbal) crossed cattle concerning their qualitative characteristics in Lombok Tengah District, Indonesia. Nusantara Bioscience 16: 104-110. Crossbreeding is a potential approach that farmers might employ to improve the productivity of Bali cattle (Bos javanicus d'Alton, 1823). Exotic cattle breeds, such as Limousin cattle (Bos taurus Linnaeus, 1758), are frequently used for crossbreeding. This study aimed to determine the qualitative characteristic differences between Bali cattle and Limousin-Bali (Limbal) crossed cattle in the Lombok Tengah District of West Nusa Tenggara Province, Indonesia. Data sampling was conducted in 2 sub-districts, namely Pringgarata and Jonggat Sub-districts. The research used 80 adult female cattle, consisting of 40 Bali and 40 Limbal cattle. The average age of cattle was 4.24 years, and the average body weight was 236.66 kg for Bali cattle and 367.88 kg for Limbal cattle. Local farmers kept cattle using the same intensive methods. Phenotypic characterization included color and physical characteristics according to the guidelines provided by the Food and Agriculture Organization (FAO) and the Indonesian Institute of Sciences (LIPI). The Data were presented descriptively, and differences across variables were assessed using the chi-square method. The research indicated no significant difference in tail-tip color (P >0.05). The body and eyelid color showed a significant difference (P <0.05). Furthermore, legs color, buttocks color, dorsal line color, vulva color, muzzle color, horn color, face profile, backline profile, horn orientation, and ear orientation differed significantly (P <0.01). Thus, it can be concluded that crossbreeding caused changes in phenotypic characteristics in the next generation. Therefore, phenotypic characterization in the next generation of these crossbreeds must be conducted, and selection criteria must be established to achieve sustainable breeding goals.